The Georgia Kaolins : Geology and Utilization. - Kogel, Jessica Elzea, 1959- (Society for Mining, Metallurgy & Exploration, Incorporated, 2002)
Annotation. "This SME handbook examines the science and business of kaolin mining and production in the southeastern United States. It provides an in-depth look at the many disciplines involved in kaolin production, including geology, mining, mineralogy, geochemistry, and microbiology. This valuable resource is written to give industry practitioners a clear understanding of how this versatile material is mined, processed, and used." "This text is an indispensable reference for geologists, mining engineers, processing plant operators, or anyone involved in the exploration, mining, or production of commercial-grade kaolin."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.
Keywords: Kaolin -- Georgia.; Kaolin industry.; elektronické knihy; electronic books